CD117 (KIT) in canine soft tissue sarcoma: an immunohistochemical and c-kit gene mutation assessment - Dell’Aere, Silvia; Balbi, Valentina; Stefanello, Damiano; Avallone, Giancarlo; Ghisleni, Gabriele; Perfetto, Stefano; Ferrari, Roberta; Auletta, Luigi; Gariboldi, Elisa Maria; Ubiali, Alessandra; Romanello, Caterina; Verdi, Alessandra; et al. (Frontiers in Veterinary Science, 2025)
IntroductionCanine soft tissue sarcomas (STSs) are locally aggressive mesenchymal tumors with variable recurrence rates, and often, their therapy is limited to surgical excision. CD117 (KIT) is a tyrosine kinase receptor involved in cell growth and cancer development. c-kit proto-oncogene mutations have been reported to be associated with prognosis and therapy response in human and canine cancers. However, CD117 expression and c-kit mutations have rarely been investigated in canine STSs. This study aims to assess CD117 expression and c-kit mutations in different canine STSs.MethodsSpontaneous STSs were surgically removed, fixed, routinely processed, and stained for histological and anti-CD117 immunohistochemical analyses. Staining intensity and percentage of positivity were scored. Cases with intense CD117 expression in more than 50% of cells were analyzed for the presence of mutations in exons 8, 9, or 11 of the c-kit proto-oncogene.ResultsOverall, 115 canine STSs were collected. Among them, CD117 was expressed in 43 STSs, with diffuse cytoplasmic staining of variable intensity. CD117 was expressed in 16 out of 27 perivascular wall tumors, 12 of 13 sarcomas of fibroblastic origin, 6 of 6 rhabdomyosarcomas, 7 of 46 liposarcomas, and 2 of 3 nerve sheath tumors. Leiomyosarcomas (20 of 20) did not show CD117 expression. Mutations were investigated in 22 cases, all of which returned negative results.DiscussionIn summary, canine STSs variably expressed CD117, which suggests that tyrosine kinase inhibitors may represent a promising targeted therapy for selected canine STSs histotypes.